Effect of mycorrhizal inoculation and organic fertiliser on bioremediation of spent engine oil contaminated soil - Nkereuwem Michael Edet; Adeleye Adeniyi Olarewaju; Karfi Uzaifa Adamu; Bashir Musbahu; Kamaldeen Fatimah (Agricultura Tropica et Subtropica, 2022)
Hydrocarbon-related environmental pollution is a major environmental hazard due to its toxicity and widespread presence in the environment, resulting in stunted growth of soil microorganisms, plants, and animals. This study was therefore conducted to evaluate the effect of mycorrhizal inoculation and compost made from Cocoa Pod Husk (CPH) and cattle dung in the bioremediation of Spent Engine Oil (SEO)-contaminated soil. About 2.5 kg of sterilised soil was contaminated with SEO at different concentrations: 0, 100, and 150 mL / pot. Compost was then added after two weeks of contamination at the rate of 10 g / pot. Inoculation for treatments containing Glomus mossaea (consisting of 20 g of root soil-fungal mixture) was blended into the soil samples as well. It was a 2 × 2 × 3 factorial experiment that was laid out in a completely randomised design and replicated three times. The incubation was allowed to last for twelve (12) weeks before the termination of the experiment. Data were collected on the Total Petroleum Hydrocarbon (TPH), bacterial and fungal biomass of the SEO-contaminated soil. Results obtained indicate that combined application of mycorrhiza with 100 mL / pot SEO resulted in significantly (p < 0.05) lower residual TPH content (54.50% degradation) of the contaminated soil compared to the other treatment combinations whereas significantly higher residual TPH content (20.43% degradation) of the contaminated soil was obtained from the interaction between 150 mL / pot SEO and without mycorrhizal inoculation. Interaction between mycorrhiza and 10 g / pot compost had a significantly higher bacterial colony (6.58 CFU / g) compared to other treatment combinations. Mycorrhizal inoculation resulted in a significantly higher fungal colony (5.844 CFU / g) compared with non-mycorrhizal inoculation (3.222 CFU / g). Therefore, it can be concluded that mycorrhizal inoculation and compost were effective in the bioremediation of SEO-impacted soil.